Impact of Harvest Periods on the Physicochemical and Flavour Characteristics of Sichuan Pepper (Zanthoxylum bungeanum Maxim) - Lian He; Yuwen Yi; Hongfeng Jia; Chengjian Xu; Mingfeng Qiao; Xuemei Cai; Sze Ying Leong; Nallammai Singaram; Sook Wah Chan; Hua Peng (Foods)
Sichuan pepper is known for its unique aroma and tingling, numbing sensation, making it a key ingredient in Sichuan cuisine. This study explored the effect of harvest periods on the quality of Sichuan pepper at five selected harvest periods (LSA (early harvest), LSB, LSC, LSD, and LSE (late harvest)) along the 24 solar terms in the traditional Chinese lunar calendar. Apart from evaluating their physicochemical and volatile profiles, the growth characteristics, polyphenol and flavonoid contents, antioxidant properties, and free amino acid and other nutrient concentrations in these peppers were also analysed. Results showed that the moisture content, weight, and shape of Sichuan peppers improved progressively, peaking at the LSE harvest period. Throughout maturation, the energy content of the Sichuan pepper remained stable. Polyphenols and flavonoids, indicators of antioxidant capacity, increased in later harvest periods. A total of 18 amino acids were detected in Sichuan pepper. Proline was the most abundant amino acid, followed by serine, arginine, and glutamic acid, accounting for 83% of the total amino acids. Based on the taste threshold values of amino acids, a taste activity value (TAV) analysis of the amino acids was conducted. The TAV analysis of arginine and glutamic acid were greater than 1, indicating their significant contribution to the bitterness and umami taste, respectively. Through the principal component analysis of the electronic tongue, it was found that Sichuan pepper picked in late July (LSA stage) had a significant difference from that picked in September (LSD and LSE stages), while the difference in taste characteristics between Sichuan pepper in early September and late September was relatively small. Terpenes were the primary volatile compounds, and the number of compounds increased as the harvest period was delayed. PLS-DA analysis revealed that D-limonene had the highest VIP value, indicating its significant contribution to the overall odour of Sichuan pepper, and thus can serve as an indicator for assessing the maturity of Sichuan pepper. This study offers valuable insights for optimising the harvesting period of Sichuan pepper and serves as a theoretical reference for enhancing the development of the seasoning industry.